2009
DOI: 10.1097/mcg.0b013e3181705ce9
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Gastroesophageal Reflux Symptoms in Obese Children Evaluated in an Academic Medical Center

Abstract: Obese children (age: 7 to 16 y) are at higher risk of having reflux symptoms compared with the control group. This risk is independent of age, sex, or race and increases with higher BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 19 publications
1
34
1
7
Order By: Relevance
“…Thus, it is possible that some of the associations reported herein are due to ‘tracking' (correlation) of adiposity from childhood through early and mid-adulthood. Alternatively, associations of childhood obesity with gastroesophageal reflux disease (Malaty et al , 2009; Pashankar et al , 2009; Ruigomez et al , 2010; Koebnick et al , 2011) and metabolic disorders may directly affect future risks of EA and GCA (Adegboye et al , 2010; Abrams and Levitt Katz, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that some of the associations reported herein are due to ‘tracking' (correlation) of adiposity from childhood through early and mid-adulthood. Alternatively, associations of childhood obesity with gastroesophageal reflux disease (Malaty et al , 2009; Pashankar et al , 2009; Ruigomez et al , 2010; Koebnick et al , 2011) and metabolic disorders may directly affect future risks of EA and GCA (Adegboye et al , 2010; Abrams and Levitt Katz, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…In adults higher body mass index (BMI) (12–14) and abdominal obesity (15) have been shown to increase the risk of developing GERD; however, data on this association in children are scarce and inconclusive. Of the three pediatric studies (16–18), two (16,17) showed a positive and one (18) no association between pediatric obesity with GERD. However, two of these studies were hospital‐based (16,18), and one included mainly asthma patients (17).…”
Section: Introductionmentioning
confidence: 93%
“…A 13% prevalence of gastroesophageal reflux has been observed in obese children (Pashankar, Corbin, Shah, & Caprio, 2009). NAFLD has been shown to occur in 2.6–25% of obese children and adolescents from small epidemiological studies using indirect diagnosis tests such as liver enzymes or ultrasound (Socha et al, 2009), while an autopsy study reported a 9.6% prevalence in children ages 2–19 years and a higher prevalence among obese children (38%) (Schwimmer, Deutsch et al, 2003).…”
Section: Consequences Of Pediatric Obesitymentioning
confidence: 99%